2015
DOI: 10.1002/ece3.1844
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation, multiple paternity, and measures of reproductive success in the critically endangered hawksbill turtle (Eretmochelys imbricata)

Abstract: The Yucatán Peninsula in Mexico contains some of the largest breeding groups of the globally distributed and critically endangered hawksbill turtle (Eretmochelys imbricata). An improved understanding of the breeding system of this species and how its genetic variation is structured among nesting areas is required before the threats to its survival can be properly evaluated. Here, we genotype 1195 hatchlings and 41 nesting females at 12 microsatellite loci to assess levels of multiple paternity, genetic variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 73 publications
1
13
0
Order By: Relevance
“…Consistent with several other studies (Wallace et al 2010, Maxwell et al 2013, 2015, the spatially explicit information presented here contributes key knowledge to marine spatial planning. The results of this study aid in the implementation of specific strategies for conservation, management and policy for the recovery of other endangered species (i.e.…”
Section: Spatially Explicit Ecological Vulnerability Of Sea Turtlessupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with several other studies (Wallace et al 2010, Maxwell et al 2013, 2015, the spatially explicit information presented here contributes key knowledge to marine spatial planning. The results of this study aid in the implementation of specific strategies for conservation, management and policy for the recovery of other endangered species (i.e.…”
Section: Spatially Explicit Ecological Vulnerability Of Sea Turtlessupporting
confidence: 89%
“…Through group dynamics, the experts ranked the threats using the CAP tool rationale in terms of their severity (magnitude and strength of the impact on sea turtle populations and their habitats), scope (geographic coverage of the threat, including whether it is punctual or impacts a wide geographic range) and irreversibility (in time, how irreversible the threats are, and if their reversibility is feasible); moreover, combined with the analytic hierarchy process (Saaty 2008, Goepel 2013), a numeric weight was assigned to each threat (Table 2). In this approach, we included a sense of time and space in the qualification of threats while updating and validating the in-water threats used in this analysis (Fig.…”
Section: Exposurementioning
confidence: 99%
“…West coast African countries are important regions as habitats for feeding and nesting of sea turtles, including hawksbills (Eretmochelys imbricata, Linnaeus, 1766) and green turtles (Chelonia mydas, Linnaeus, 1758) (Formia et al, 2003), two species respectively considered as critically endangered and as endangered, according to The IUCN Red List of Threatened Species (Camacho et al, 2013;González-Garza et al, 2015;Orós et al, 2005). Mortality causes include direct and indirect anthropogenic activities, such as fishing, trauma and pollution, but these animals can also be affected by neoplasia and infectious diseases, namely pneumonia, hepatitis, meningitis and septicemia (Óros et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, only one study to date has investigated connections between genetic variation and phenotypic traits related to fitness in marine turtles, and there were no significant relationships between measures of reproductive success (i.e., clutch size, hatching success, and frequency of infertile eggs) and neutral nuclear loci in hawksbill turtles (Gonzalez-Garza et al, 2015). However, examination of functional genomic regions (MHC loci) in loggerhead turtles suggested that locally adapted pools of MHC alleles at the margins of the population distribution combined with male-mediated gene flow may be key to sustaining adaptive potential across the entire rookery (Stiebens et al, 2013a,b).…”
Section: How Do Recent Population Declines Affect Marine Turtle Long-mentioning
confidence: 97%
“…However, a recent study in olive ridley turtles in Mexico discerned a human-induced contemporary bottleneck across an entire metapopulation where strong impacts of a commercial fishery from 1960 to 1990 significantly reduced allelic diversity (Rodríguez-Zárate et al, 2013) as well as phenotypic variation of reproductive modes (i.e., solitary nesters vs. arribadas; AbreuGrobois and Plotkin, 2008). Additionally, lower levels of genetic variation in younger vs. older turtles were recently reported in Yucatan peninsula hawksbills (Gonzalez-Garza et al, 2015), which is the largest nesting population in the Atlantic and critical for long-term hawksbill persistence (Mortimer and Donnelly, 2008). This work highlights that although marine turtles have buffers to maintain genetic diversity in the face of human-driven declines, they are not completely immune, and once it is lost it would likely take a long time to regenerate (i.e., low diversity may persist even as abundances of depleted populations recover).…”
Section: How Do Recent Population Declines Affect Marine Turtle Long-mentioning
confidence: 99%